Exploring the impact of Quebec's vaccine lottery and vaccine passports on Covid-19 vaccination intention: Findings from repeated cross-sectional surveys. Issue 6 (30th November 2022) - Dubé, Ève; Dionne, Maude; Rochette, Louis
ABSTRACT: In Quebec, during the summer of 2021, different strategies to enhance COVID-19 vaccine uptake were implemented (e.g. mobile vaccination clinics, mass communication campaigns, home vaccination). The aim was that at least 75% of 12 years and older individuals receive two doses of COVID-19 vaccines before the fall. This article explores the impact of incentives and disincentive strategies on Quebecers' intention to be vaccinated against COVID-19. A series of cross-sectional surveys have been ongoing in Quebec since March 2020 to measure Quebecers' attitudes and behaviors during the pandemic. In July and August 2021, in addition to sociodemographic information, the survey assessed COVID-19 risks perceptions, adherence to and perception of recommended measures (e.g. masks, physical distancing, vaccine lottery, vaccine passport) as attitudes and intention toward COVID-19 vaccines. Descriptive statistics were generated. Between July 9 to September 1, the vaccine uptake (two doses) rose from 62% to 88%. Among respondents who were unvaccinated during the period, 32% reported a positive influence of the lottery on their intention to be vaccinated against COVID-19 and 39% for the vaccine passport. Approximately half (51%) of unvaccinated respondents reported no influence from the two measures, and both positively influenced 20%. The vaccine lottery had a limited impact on willingness to receive COVID-19 vaccines among unvaccinated adults in Quebec, but the implementation of the vaccine passport appears more influential based on survey respondents' responses.